The role of POAC management functions in enhancing the quality of counseling guidance services for students in schools in Indonesia - Asni, Asni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Guidance and counseling (BK) services in schools often face issues such as lack of coordination, limited resources, and low student participation. These challenges stem from the suboptimal implementation of the POAC (Planning, Organizing, Actuating, and Controlling) management functions by school counselors. This study aims to analyze the influence of each POAC function on the quality of BK services in junior high schools (SMP) in South Jakarta. The research employs a quantitative approach, with data collected through surveys of 52 BK teachers. Quantitative data were analyzed using multiple linear regression.The results indicate that all POAC variables significantly influence the quality of BK services (p-value < 0.01). Planning has the strongest influence (β = 0.01), followed by organizing (β = 0.00), actuating (β = 0.00), and controlling (β = 0.00). Collectively, the POAC functions explain 72% of the variation in the quality of BK services. In conclusion, the optimal implementation of POAC functions can enhance the quality of BK services. This study recommends management training for BK teachers and the development of operational guidelines for effective POAC implementation. The findings provide practical contributions to improving BK services in schools and enrich empirical evidence on the importance of POAC management in the context of Indonesian education.